A pilot study of oral treprostinil pharmacogenomics and treatment persistence in patients with pulmonary arterial hypertension. (April 2021) - Coons, James C.; Crisamore, Karryn; Adams, Solomon; Modany, Ashley; Simon, Marc A.; Zhao, Wenchen; Shaik, Imam H.; Venkataramanan, Raman; Empey, Philip E.
Background and aims: Treprostinil is a prostacyclin analog used to treat pulmonary arterial hypertension. Dosing is empiric and based on tolerability. Adverse effects are common and can affect treatment persistence. Pharmacogenomic variants that may affect treprostinil metabolism and transport have not been well-characterized. We aimed to investigate the pharmacogenomic sources of variability in treatment persistence and dosing. Methods: Patients were prospectively recruited from an IRB approved biobank registry at a single pulmonary hypertension center. A cohort of patients who received oral treprostinil were screened for participation. Pharmacogenomic analysis was for variants in CYP2C8, CYP2C9, and ABCC4 . A retrospective review was conducted for demographics, clinical status, dosing, and response. Fisher's exact test was used for categorical data and Kruskal–Wallis test or Wilcoxon rank sum were used for continuous data. Results: A total of 15 patients received oral treprostinil and were consented. Their median age was 53 years, 73% were female, and 93% were White. The median total daily dose was 22.5 mg (13.5, 41) at last clinical observation. 40% of patients discontinued treatment with a majority due to adverse effects. Approximately 27% of patients had a loss-of-function variant in CYP2C8 (*1/*3 or *1/*4), whereas 47% of patients had a loss-of-function variant in CYP2C9 (*1/*2, *1/*3, or *2/*2). Minor allele frequencies for ABCC4 (rs1751034 and rs3742106) were 0.17 and 0.43, respectively. Survival analysis showed that increased CYP2C9 activity score was associated with decreased risk for treatment discontinuation [hazard ratio (HR): 0.13; 95% confidence interval (CI): 0.02, 0.91; p = 0.04]. Genetic variants were not significantly associated with dosing. Conclusion: Genetic variants responsible for the metabolism and transport of oral treprostinil were common. Increased CYP2C9 activity score was associated with decreased risk for treatment discontinuation. However, dosing was not associated with genetic variants in metabolizing enzymes for treprostinil. Our findings suggest significant variability in treatment persistence to oral treprostinil, with pharmacogenomics being a potentially important contributor. The reviews of this paper are available via the supplemental material section.